Development of Offline E-Modules to Improve Learners’ Academic Performance in Disciplines and Ideas in the Social Sciences - Rocky Lou N Aniciete; Anacleta M Cabigao; Ma Lorena M Tagala; Alfredo G Perez Jr; Eulalia M Javier (Research Synergy Foundation, 2022)
As the education system in the Philippines has adapted to distance learning due to the global pandemic, self-learning modules also have become the primary learning resources of the learners. However, many modules distributed to learners were criticized due to erroneous contents, level of difficulty, number of tasks, and printing costs. Meanwhile, there were lack of modules for specialized subjects in some public senior high schools. In this regard, this study attempted to develop and validate offline yet electronic modules in one of the specialized subjects in senior high school, Disciplines and Ideas in the Social Sciences (DISS). In developing these, the study used Normative Design and Analysis, Design, Develop, Implement, and Evaluation (ADDIE) model. Twenty (20) Social Science and five (5) ICT teachers in the Division of Biñan City were asked to validate the developed e-modules, while thirty (30) learners from Biñan Integrated National High School were asked to participate in the Implementation Phase. An adopted questionnaire was given to the validators to assess the e-modules’ validity and acceptability while pretests and post-tests were given to the participating learners. Through the ADDIE model, the study was able to design and develop offline e-modules named Disciplines and Ideas in the Social Sciences Knowledge-Amplifying Remote Training E-Modules (DISSKARTE). Using the four-point Likert Scale and the simple mean, findings revealed that its objectives, concepts, topics, directions, exercises, and reflections were all highly valid. The findings showed that its functionality, accuracy, suitability, usability, and efficiency were all highly accepted. Pretest results showed that most of the participants did not meet expectations while the post-test results revealed otherwise as the majority got outstanding and very satisfactory remarks. T-test for dependent means revealed that there were significant differences in the pretests and post-tests. This implied that through DISSKARTE, the learners’ performance on DISS can improve. The study is limited to developing e-modules covering only a quarter of DISS subject. However, it is hoped that the study was able to contribute to the world of literature as there were only few to zero studies about developing instructional materials for DISS especially in the context of new normal.